Meta-analyses of associations between interleukin-10 polymorphisms and susceptibility to recurrent pregnancy loss. (May 2016) - Lee, Young Ho; Kim, Jae-Hoon; Song, Gwan Gyu
Abstract: Objective: The aim of this study was to investigate whether interleukin-10 (IL-10) polymorphisms are associated with susceptibility to recurrent pregnancy loss (RPL). Methods: We conducted a literature search using the PubMed and EMBASE databases and performed meta-analyses on the associations between IL-10 −1082 G/A, −819 C/T, and −592 C/A polymorphisms and RPL, using fixed- or random-effects models. Results: A total of 15 papers involving 1858 RPL patients and 1949 controls were considered in this study. Meta-analysis of IL-10 −1082 G/A polymorphism revealed no association between RPL and the IL-10 −1082 G allele (OR = 0.999, 95% CI = 0.815–1.223, p = 0.989). However, meta-analysis of IL-10 −819 C/T polymorphism in all study subjects revealed an association between RPL and the IL-10 −819 C allele (OR = 0.680, 95% CI = 0.498–0.927, p = 0.015). Stratification by ethnicity indicated an association between the IL-10 −819 C allele and RPL in the Asian group (OR = 0.421, 95% CI = 0.226–0.783, p = 0.006), but not in the Caucasian and Arab groups (OR = 1.053, 95% CI = 0.218–5.077, p = 0.949, and OR = 0.800, 95% CI = 0.606–1.081, p = 0.152, respectively). Furthermore, a relationship between the IL-10 −592 C allele and RPL was identified in the Asian group (OR = 0.763, 95% CI = 0.633–0.919, p = 0.004), but not in the Caucasian and Arab groups. Conclusions: The meta-analyses demonstrate that IL-10 −819 C/T and −592 C/A polymorphisms are associated with RPL susceptibility in Asian women, but not in the Caucasian and Arab populations.